Geospatial Data, Information, and Intelligence - Jabbour, Aaron; Babiarz, Renny (Artech, 2023)
This book provides practitioners with structured methods for transforming geospatial data into the useful information they need to solve some of the world’s most pressing problems. It spotlights the importance of location for human experience in the everyday world and introduces spatial thinking as a foundation and the location mindset as a foundational perspective. The book starts by showing how geospatial analysis is part of a more general data-to-information refinement process that requires the right mindset, toolset, and skillset to achieve. The book then presents structured principles and practices to help geospatial analysts—whether in government or industry—improve their observational, analytical, and communication techniques. These techniques are part of an original framework for interpreting geospatial data and information: the Observe, Analyze, Communicate (OAC) Framework. The OAC framework helps practitioners at all levels break down the basic steps of their day-to-day practice and learn valuable tradecraft that they can employ during each step. You’ll learn how to center location as a foundational perspective in everyday life; use unique geospatial observation, analysis, and communication techniques; and know how to account for the role of uncertainty in assessment and production processes -- including utilizing special techniques to effectively communicate levels of certainty and uncertainty to your audience. You’ll also understand how pairing visual information with precise locational information serves to anchor human attention and provides an antidote to the common problem of disorientation. The book reveals specific techniques and tradecraft that will greatly benefit all practitioners working with visual and locational information. One such tradecraft called Structured Geospatial Observation Techniques (SGOT) includes a technique called the Four Cornerstones that will allow you to structure your approach to visual data and extract more attribute and contextual data from your object of focus. Another technique reveals industry and government-gleaned tips and tricks to creating finished geospatial communications in paragraphs, products, and presentations. Bringing together the authors’ combined 30 years of experience with geospatial intelligence (GEOINT), this book is a must-have practical resource for students, faculty, and practitioners of geospatial endeavors at any level of experience, especially fields that use imagery and spatial analysis. It serves as a textbook for classroom beginners and as a go-to desktop reference for professionals in their day-to-day geospatial efforts.